Pengaruh PPN Masukan dan PPN Keluaran Terhadap Hutang Pajak di CV Guyub Rukun - Suratno Suratno (Publikasi Indonesia, 2022)
The purpose of this study was to determine the effect of input VAT and output VAT on tax payables at CV Guyub Rukun. This study uses a descriptive method with a quantitative approach. The data analysis technique is based on Law Number 42 of 2009 concerning the value added tax of goods and services and sales tax on luxury goods. The calculation results show that the VAT tax payable in 2020 has increased from Rp. 11,100,000 to Rp. 11,200,000 or 0.90%. The increase was due to the difference between purchases and sales in 2020 of 6.52%. Meanwhile, in 2021 it decreased from Rp. 11,200,000 to Rp. 9,450,000 or 0.16% due to the difference between purchases and sales in 2021 by 5% or smaller than 2020.